Penerapan Tri Hita Karana untuk Keberlanjutan Sistem Subak yang Menjadi Warisan Budaya Dunia: Kasus Subak Wangaya Betan, Kecamatan Penebel, Kabupaten Tabanan - Fajar Kartika Lestari, Putu; Windia, Wayan; Sri Astiti, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 3 No 1 (2015): Vol. 3 - No. 1 - Mei 2015, 2015)
The cornerstone of Subak system which used to managing the organization is harmony foundation of harmony and togetherness, which manifest by Tri Hita Karana concept (THK) Parhyangan, Pawongan, and Palemahan. Noble values contained in Subak make UNESCO (United Nations Educational, Scientific and Cultural Organization) determine subak as a World Cultural Heritage (WBD). This research aims to analysis the implementation of THK for sustainability of subak system. The analysis techinique used for this is descriptive qualitative and quantitative analysis. The results of matrix inverse analysis is the relation between all the sub-system from system technology and all the culture sub-system could describe subak sustainability and the application of Tri Hita Karana (THK) concept at Subak Wangaya Betan. The result of matrix inverse analysis is describe the sustainability capabilities of Tri Hita Karana at Subak Wangaya Betan by 30,27%. This result is caused by the elements still lacking in its implementation on an ongoing basis. As expected, Tri Hita Karana concept which prioritize harmony and togetherness could be applied to all the components of subak. Application of Tri Hita Karana at subak could be improved with the aim to sustain Subak Wangaya Betan activities that have been executed.
Keywords: subak, tri hita karana, the world cultural heritage, sustainability